The politics of natural disasters in protracted conflict: the 2014 flood in Kashmir. (2nd October 2017) - Venugopal, Rajesh; Yasir, Sameer
Abstract: This paper explores the politics of the 2014 floods in the contentious and conflict-prone Indian state of Jammu and Kashmir. The September 2014 floods were the most serious natural disaster in the state in the past 60 years, and affected some two million people in the Kashmir valley. Drawing on qualitative interview evidence from 50 flood victims in south, central and north Kashmir, the paper examines the extent to which the disaster transformed existing political narratives. In doing so, it examines the role of the state and central governments, the army, local volunteers, and the media. The paper engages with the politics of disaster literature, exploring how disasters can serve as a lens rather than as a catalyst, and stressing the relevance of understanding the social construction of disaster narratives.